Comparison of the Quality of Flaw Detection Materials Using Samples Developed for Liquid Penetrant Testing; Materials Science Forum; Vol. 970 : Modern Problems in Materials Processing, Manufacturing, Testing and Quality Assurance II - Kalinichenko A. N. Aleksey Nikolaevich (2019, 2019)
Title screen